Text as Ride : Electronic Literature and New Media Art - Strehovec, Janez, 1950- (Book collections on Project MUSE., 2016)
Text as Ride re-situates our understanding of new media in the social contexts of mobile apps, thrill rides, walking in the city, 3D cinema, video games, and DJ culture. Rather than a continuation of print-based literature by other means, this book considers electronic literature as a practice that foregrounds new media's specificity. Janez Strehovec deals with post-hypertext eLiterature that has become conceptual: Moving beyond hyperlinked storytelling, it deals with digital materiality and boundaries of language; with code, textual ecology, and the limits of the sayable. This book will appeal to scholars of electronic literature, gaming, urban studies, cinema, and digital culture.